Politics Under Conditions of War: the effect of the War Measures Acts on Political Struggles within the South African Mine Workers’ Union, 1939-1947 - Visser, Wessel (Scientia Militaria - South African Journal of Military Studies, 2016)
The South African Mine Workers’ Union, or MWU, was one of the most prominent white trade unions of 20th-century South Africa and active in one of the country’s key industries, namely gold mining. In the aftermath of the violent 1922 strike, the union’s executive was bureaucratised, which left the MWU vulnerable to corruption and maladministration. This gave rise to a protracted struggle for control of the union’s executive. In the 1930s and 1940s the strife within MWU ranks became entangled with the national struggle for political hegemony between the National Party and the United Party, as well as Afrikaner nationalism. At the outbreak of World War II the Smuts cabinet armed the state under War Measures’ Acts, which entitled it to a range of arbitrary powers, including powers to control strategic minerals, such as gold, and to curb industrial unrest. Naturally, the War Measures’ Acts had a significant effect on the doings of the MWU – in particular the struggle for political control of its executive. The struggle involved three official commissions of inquiry into the affairs of the MWU, two mining strikes and numerous court actions between the two competing factions within its ranks. As a result of the stipulations of the War Measures’ Acts pertaining to the mining industry, as well as those of the MWU constitution, a political impasse to solve the issue of democratic elections in the union arose. Therefore the War Measures’ Acts still had legal repercussions for the union three years after the cessation of hostilities. As such, the War Measures’ Acts[i]influenced politics and elections in the MWU as late as 1948.